Determination of Thiocyanate by Kinetic Spectrophotometric Flow Injection Analysis. (2nd July 2012) - Keyvanfard, Mohsen; Alizad, Khadijeh; Elahian, Parinaz
Abstract : A simple and rapid flow injection spectrophotometric method has been developed for the determination of amount of thiocyanate in wastewaters and well water samples. It is based on the reaction of thiocyanate in hydrochloric acid with janus green and bromate. Reaction was monitored spectrophotometrically by measuring janus green absorbance at λ max = 554 nm. The calibration graph was linear over the range 0.02–1.0 μ g mL −1 and the detection limit was 0.016 μ g mL −1 (s/n = 3 ). The throughput was 25 samples per hour.